Stable Spillovers among Substitutes - Veendorp, E. C. H. (Review of Economic Studies, 1975)
Journal Article Stable Spillovers among Substitutes Get access E. C. H. Veendorp E. C. H. Veendorp Tulane University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 3, July 1975, Pages 445–456, https://doi.org/10.2307/2296857 Published: 01 July 1975